Coated rubber granulates obtained from used tyres for use in sport facilities: A toxicological assessment - Mota,H. I (2009)
Reuse of tire crumb in sport facilities is currently a very cost-effective waste management measure. Considering that the incorporation of the waste materials in artificial turf would be facilitated if the rubber materials are already coloured of green, coatings were developed for this purpose. This study presents the toxicological and environmental assessment made comparing the obtained emissions to the environment in terms of PAHs, heavy metals and Ecotoxicity for coated and non-coated rubber granulates. It was concluded that, among two types of coatings tested, one is particularly effective in reducing emissions to the environment meeting, at the same time, the requirements of adherence and colour stability.